Survival of National Research and Education Networks (NRENs) in a competitive market of Africa: A Case Study of the Zambia Research and Education Network (ZAMREN) - Mkandawire, Stein (My University, 2013)
The proliferation of not for profit associations called National Research and Education Networks (NRENs) on the African market particularly in the area of Broadband Internet provision has made commercial Internet Service Providers (ISPs) develop apprehensions against NRENs. What is happening is that NREN’s are being viewed as competitors by commercial ISPs. However, the truth of the matter is that commercial ISPs should consider NRENs as incubators of technology users that will grow their market base. In the absence of this realisation by commercial ISPs, NRENs are likely to face stiff competition which will in turn adversely affect the survival of NRENs. This paper suggests measures that NRENs should employ to survive in a competitive African market.
Keywords: Survival of NRENs; Competitive market of Africa; NRENs; ZAMREN; ISP